Can digital health literacy promote residents’ physical and mental health? An empirical analysis based on Chinese General Social Survey - Wei, Pingqiang; Jia, Haigang (Frontiers in Public Health, 2025)
With the rapid development of digital technology, the role of digital health literacy in improving the physical and mental health of residents has become increasingly prominent. Based on the survey data of CGSS2021, this study selected 1805 valid samples. Multiple linear regression model and Bootstrap mediating effect test were used to explore the impact of physical exercise, social interaction and digital health literacy on residents’ physical and mental health. The results show that: (1) Digital health literacy has a significant positive impact on residents’ physical and mental health (physical health: β = 0.146, p < 0.05; mental health: β = 0.752, p < 0.01); (2) Participation in physical exercise and social networks have a mediating role in the impact of digital health literacy on residents’ physical and mental health, and have a chain mediating role; (3) Digital health literacy promotes residents’ physical and mental health, but there is heterogeneity. In rural areas and women with low or normal BMI, the improvement of digital health literacy has a significant effect on physical health. In the male group of urban residents, the improvement of digital health literacy has a significant effect on mental health. Based on this, we propose: First, strengthen the promotion of digital health literacy education, especially the digital health literacy level of residents and women in rural areas. Second, encourage residents to actively participate in physical exercise, physical exercise as a link to promote the physical and mental health of residents. The third is to promote the development of social interaction activities, and various organizations expand social support networks to provide strong support for residents’ mental health.